An Aplysia-like synaptic switch for rapid protection against ethanol-induced synaptic inhibition in a mammalian habit circuit. (January 2019) - Patton, Mary H.; Padgett, Katherine E.; McKeon, Paige N.; Lu, Shao-Gang; Abrams, Thomas W.; Mathur, Brian N.
Abstract: Decades of work in Aplysia californica established the general rule that principles of synaptic plasticity and their molecular mechanisms are evolutionarily conserved from mollusks to mammals. However, an exquisitely sensitive, activity-dependent homosynaptic mechanism that protects against the depression of neurotransmitter release in Aplysia sensory neuron terminals has, to date, not been uncovered in other animals, including mammals. Here, we discover that depression at a mammalian synapse that is implicated in habit formation and habit learning acceleration by ethanol, the fast-spiking interneuron (FSI) to medium spiny principal projection neuron (MSN) synapse of the dorsolateral striatum, is subject to this type of synaptic protection. We show that this protection against synaptic depression is calcium- and PDZ domain interaction-dependent. These findings support activity dependent protection against synaptic depression as an Aplysia -like synaptic switch in mammals that may represent a leveraging point for treating alcohol use disorders. Highlights: A novel mammalian synaptic plasticity mechanism protects against long-term synaptic depression (LTD) in the dorsolateral striatum. Burst-dependent protection against LTD is Ca2+ and PDZ domain-dependent. This protection occurs in Aplysia californica and is possibly evolutionarily conserved.